INTRAMEDULLARY SPINAL CORD METASTASES: REVIEW OF THE LITERATURE - Hrabalek, Lumir (Biomedical papers, 2010)
Aims: To review the epidemiology, dissemination, clinical presentation, diagnosis, treatment, survival and functional outcome of intramedullary spinal cord metastases (ISCM).Methods: Literature review of all surgically treated cases of ISCM and all described cases of ISCM of breast carcinoma.Results: 42 references to 87 surgically treated cases of ISCM were found, 13 references to 27 cases with diagnosed and treated ISCM of breast carcinoma. In only 9 cases of spinal cord metastases of breast cancer was surgical resection of ISCM done (10% of all surgically treated ISCM).Conclusions: Three treatment modalities are available for ISCM: radiotherapy, chemotherapy, and surgery. The gold standard remains radiotherapy. Microsurgical resection of a focal intramedullary mass appears to be feasible and should be considered in selected cases. Patients who have no evidence of widespread organ metastases or multiple intramedullary lesions and who have a life expectancy of at least a few months with tumours of non-lymphoma histology should be considered for tumor resection. In conclusion, ISCM are difficult to treat lesions, but early diagnosis, careful surgical management and maintenance therapy may substantially contribute to a satisfactory functional outcome and prolonged survival.
Keywords: Intramedullary/Spinal cord/Metastasis/Breast cancer/Surgery/Leptomeningeal disease